Telomere biology: from disorders to hematological diseases - Roka, Kleoniki; Solomou, Elena E.; Kattamis, Antonis (Frontiers in Oncology, 2023)
Variations in the length of telomeres and pathogenic variants involved in telomere length maintenance have been correlated with several human diseases. Recent breakthroughs in telomere biology knowledge have contributed to the identification of illnesses named “telomeropathies” and revealed an association between telomere length and disease outcome. This review emphasizes the biology and physiology aspects of telomeres and describes prototype diseases in which telomeres are implicated in their pathophysiology. We also provide information on the role of telomeres in hematological diseases ranging from bone marrow failure syndromes to acute and chronic leukemias.